The Parable of the Prodigal Father: An Interpretative Key to the Third Gospel (Luke 15:11-32) - Trevor J. Burke (Tyndale Bulletin, 2013)
Agreement on a title for the parable in Luke 15:11-32 has proved problematic for interpreters: is this primarily a story about the ‘son’ or ‘sons’ or a ‘family’? While such descriptions are viable, they are insufficient and the view taken in this essay, along with that of an increasing number of scholars—not discounting the role of the two sons—is to approach the story from a paternal perspective. Moreover, this parable is about a ‘prodigal father’ for his extravagant generosity and liberality is highly unusual and unexpected. Such conduct, however, is no less a part of the evangelist’s wider agenda of ‘prodigality’ in the third Gospel, where the same munificence and largesse are characteristics consonant with those who belong in the kingdom of God. It is concluded that if the father is representative of God in his reckless beneficence then another legitimate designation for this narrative should be ‘The Parable of the Prodigal Father’.